The Covid-19 Pandemic And Online Learning: Challenges For University Students - Wiratman, Arwan; Rahmadani, Ervi (ETDC: Indonesian Journal of Research and Educational Review, 2022)
Covid-19 forced the government to stop offline or face-to-face learning and implement online learning. Online learning is a new learning style for most students. This study investigates the challenges of online learning faced by students at a faculty of education in South Sulawesi. In particular, this research focuses on the types of challenges faced by students and how they overcome these challenges. This study uses a qualitative approach by conducting semi-structured interviews via telephone calls, WhatsApp applications, and virtual zoom applications to collect data from 30 students at one campus in South Sulawesi. The findings of this study indicate that the challenges faced by students are largely influenced by digital knowledge and skills, economic background, place of residence, and the teaching style of lecturers. This study concludes that online learning is less effective in increasing student participation, activeness, and providing quality learning.